If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+2u=5u
We move all terms to the left:
6+2u-(5u)=0
We add all the numbers together, and all the variables
-3u+6=0
We move all terms containing u to the left, all other terms to the right
-3u=-6
u=-6/-3
u=+2
| 4g-13=31 | | h-19=2 | | 22x+2(3x+5)=21 | | .35x=10 | | 5(2c-2)-2c=25 | | 36=25+x | | 12x=8+8x | | 65+0.70x=0.90x | | 63=7(a+9) | | 2(2-x)=46 | | 40+k=51 | | w-12=14 | | 4(y-8)=9y-12 | | 3.6a=7.2 | | 30=5(x/5-3 | | 2.5x+5=40 | | 4.5=x/18 | | x^2+10x+67=0 | | 180=2x+6x+x | | 7(x41)-1=34 | | 8a+4=3a+24 | | 90+(x+6)+2x=180 | | 65x=85x+170 | | 7/9w=10 | | 9h/16=65 | | t/6-5=3 | | 9.6+m=10.4 | | 6q43-4q=9 | | -34=-(4a-2)-8(a+4) | | 6q43-4=9 | | 699+0.55x=11.94 | | 7n-3=25* |